Exceeding the Limits of Static Cold Storage in Limb Transplantation Using Subnormothermic Machine Perfusion - Goutard, Marion; de Vries, Reinier J.; Tawa, Pierre; Pendexter, Casie A.; Rosales, Ivy A.; Tessier, Shannon N.; Burlage, Laura C.; Lantieri, Laurent; Randolph, Mark A.; Lellouch, Alexandre G.; Cetrulo Jr, Curtis L.; Uygun, Korkut (Journal of Reconstructive Microsurgery, 2022)
Background For 50 years, static cold storage (SCS) has been the gold standard for solid organ preservation in transplantation. Although logistically convenient, this preservation method presents important constraints in terms of duration and cold ischemia-induced lesions. We aimed to develop a machine perfusion (MP) protocol for recovery of vascularized composite allografts (VCA) after static cold preservation and determine its effects in a rat limb transplantation model.Methods Partial hindlimbs were procured from Lewis rats and subjected to SCS in Histidine-Tryptophan-Ketoglutarate solution for 0, 12, 18, 24, and 48 hours. They were then either transplanted (Txp), subjected to subnormothermic machine perfusion (SNMP) for 3 hours with a modified Steen solution, or to SNMP + Txp. Perfusion parameters were assessed for blood gas and electrolytes measurement, and flow rate and arterial pressures were monitored continuously. Histology was assessed at the end of perfusion. For select SCS durations, graft survival and clinical outcomes after transplantation were compared between groups at 21 days.Results Transplantation of limbs preserved for 0, 12, 18, and 24-hour SCS resulted in similar survival rates at postoperative day 21. Grafts cold-stored for 48 hours presented delayed graft failure (p = 0.0032). SNMP of limbs after 12-hour SCS recovered the vascular resistance, potassium, and lactate levels to values similar to limbs that were not subjected to SCS. However, 18-hour SCS grafts developed significant edema during SNMP recovery. Transplantation of grafts that had undergone a mixed preservation method (12-hour SCS + SNMP + Txp) resulted in better clinical outcomes based on skin clinical scores at day 21 post-transplantation when compared to the SCS + Txp group (p = 0.01613).Conclusion To date, VCA MP is still limited to animal models and no protocols are yet developed for graft recovery. Our study suggests that ex vivo SNMP could help increase the preservation duration and limit cold ischemia-induced injury in VCA transplantation.
Keywords: preservation; reconstructive surgery; VCA; cold storage; machine perfusion; transplantation